Does religion affect alcohol and tobacco use among students at North-West University, South Africa? (2017)
The present study used multidimensional measures of religion to asses religion's influence in engedering positive behavioursas measured by alcohol and tobaco use among a sample of undergraduate students at the North-West University in South Africa. Multinomial logistic regression model was used to examine the effect of religion on youth alcohol and tobaco use. Zero-order correlations showed that measures of religion not only correlated positively with each other, but they correlated negatively with both current use of alcohol and tobacco. Religious affiliation was insignificant, but self-related religiosity was positvely associated with drinking among females who reported that they always drink alcohol, frequency of church attendance increased the odds of drinking among females who reported that they never drink compared to those who reported that they drink occasionally. Social class, as measured by father's education was negatively associated with both alcohol and tobacco use. On the whole, religious commitment continues to act as the protective factor against these two anti-social behaviours of teh youth.